Using reciprocal teaching strategy to improve physics students’ critical thinking ability - Mafarja, Nofouz (Eurasian Society of Educational Research, 2022)
In Palestine, issues about word problem solving and physics critical thinking have led to a deep understanding of factors affecting physics problem solving among Palestinian students. The influence of Reciprocal Teaching on physics students’ critical thinking skills among 10th-grade students in Palestine was investigated in the study. The study used a quasi-experimental research design. Two treatment groups (male and female) and two control groups were randomly allocated to four intact courses (male and female). All four groups included a total of 120 participants who were preand post-tested on their critical thinking skills in physics. Preliminary checks were performed prior to inferential testing to ensure that the one-way MANCOVA assumptions were not violated. After adjusting for physics word problem-solving pre-test scores for critical thinking skills, one-way MANCOVA results show that reciprocal teaching strategy has a considerable effect on critical thinking skills at p<.05 level between the groups F(1, 118)=336.649, p=.001˂.05. In addition, the two-way MANCOVA results for the interaction effect of gender and method is not large in critical thinking skills, with F(1, 116)=3.5, p=.064>.05 but is big in two sub-skills interpretation, with F(1, 116)=5.187, p=.025˂.05, and evaluating arguments skill, with F(1, 116)=5.463, p=.021˂.05 in favour for male students. As a result, using a reciprocal teaching technique to learn physics topics is more effective than using a standard method, and it is applicable and effective for both male and female students. This study has implications for policymakers to encourage the implementation of an integrated reciprocal teaching strategy in schools. It also has implications for teachers’ instructional practices in the classroom. © 2022